CURRENT PROBLEMS WITH INTRACANALICULAR FALLOPIAN TUBE OBSTRUCTION (Literature review) - Gulsanam B. Malikova; Bakhtiyor M. Abdurahmonov (Central Asian Journal of Medicine, 2023)
The most common cause of tubal obstruction is inflammation. It may be due to sexually transmitted diseases, infectious complications after abortion. According to the literature data, fallopian tubes patency after an infectious process is more often impaired in the ampullary and less often in the interstitial region. This is due to the peculiarities of blood supply in the ampullary sections of the fallopian tubes by the type of venous lacunas and arteriovenous anastomoses, with the predominance of ciliated epithelium, unstable to damaging factors, especially infectious nature. These anatomo-physiological features predetermine the predominant involvement of the ampullary parts of the fallopian tubes, regardless of the type of infection and its route of entry into the tube. In chlamydial, mycoplasma, gonococcal, viral and other ascending infections, adhesions and obliterations develop in the fallopian tubes, resulting in complete or partial tubal occlusion due to epithelial and/or muscular layer lesions, leading to compression of the tube from outside, Pathological curvature of the tubes, impaired contractile function, fimbriae, peritubular and ovarian adhesions, reduced number of endosalpinx cilia, resulting in impaired function of the fallopian tubes in receiving and feeding the egg, sperm and embryo, gamete and embryo transport.